(3YeOI GdEUdGM aj Yed UfGYI GdLQGMs - (3jYbhH Hf ESMGb GdeSjMj Gdedcj GdcQcj GHf Gdba, CHh GdaQL,J (B685 (3g` s ((3SaM bGHShf s)
(3ChdgG (B:s
(3hHYO abO TcG Edi HYV LQGMi ReGffG bdI EgJeGe CQHGH gPG Gdaf HCeQ gPg GdUfGYI Cfi CUfa dg cJGHkG aj Pdc , hCf CPcQ ChdG MO gPg GdUfGYI s
(3BNQgG (B:s
(3hRf QWd Ke ScQ fbi hRf QWdjf jOb hjVGa Edjg ChdG aChd , hjLYd aj TeS MGQI hjSJYed hGddg SHMGfg CYde s
(3QJHg Ydi YTQjf ebGdIs
(3fSNI Yf fSNI eShOI HNW GdeDda SfI(B676(3g`s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs